PK1 from Drosophila obscurin is an inactive pseudokinase with scaffolding properties. Issue 4 (26th April 2023) - Zacharchenko, Thomas; Dorendorf, Till; Locker, Nicolas; Van Dijk, Evert; Katzemich, Anja; Diederichs, Kay; Bullard, Belinda; Mayans, Olga
Abstract : Abstract : Obscurins are large filamentous proteins with crucial roles in the assembly, stability and regulation of muscle. Characteristic of these proteins is a tandem of two C-terminal kinase domains, PK1 and PK2, that are separated by a long intrinsically disordered sequence. The significance of this conserved domain arrangement is unknown. Our study of PK1 from Drosophila obscurin shows that this is a pseudokinase with features typical of the CAM-kinase family, but which carries a minimalistic regulatory tail that no longer binds calmodulin or has mechanosensory properties typical of other sarcomeric kinases. PK1 binds ATP with high affinity, but in the absence of magnesium and lacks detectable phosphotransfer activity. It also has a highly diverged active site, strictly conserved across arthropods, that might have evolved to accommodate an unconventional binder. We find that PK1 interacts with PK2, suggesting a functional relation to the latter. These findings lead us to speculate that PK1/PK2 form a pseudokinase/kinase dual system, where PK1 might act as an allosteric regulator of PK2 and where mechanosensing properties, akin to those described for regulatory tails in titin-like kinases, might now reside on the unstructured interkinase segment. We propose that the PK1-interkinase-PK2 region constitutes an integrated functional unit in obscurin proteins.